Encyclopedia of Industrial Biotechnology 2009
DOI: 10.1002/9780470054581.eib431
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Induced Corrosion and Inhibition

Abstract: Microbial corrosion refers, by definition, to the degradation of materials due to the activity of a wide variety of microorganisms, usually embedded in a gel matrix—the biofilm—attached to the surface. The feature of MIC (microbial induced corrosion) is connected to three factors: microorganisms involved (bacteria, algae, moulds or fungi, individually or in combination), material, and environment (solution and conditions). In particular, degradation of metallic structures derives from the activity of a wide va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Increased hydrodynamic resistance, caused by drag forces from the roughened ship hulls, raises fuel consumption and leads to higher emissions and costs for fuel (by up to 40%) 5 as well as time-and resource-consuming cleaning procedures. 4,6,7 Some microorganisms, e.g., sulfatereducing (SRB), sulfur-oxidizing (SOB), iron-oxidizing (IOB), or iron-reducing (IRB) bacteria, can cause MIC through their bio-lms and metabolic products, 8,9 and thus compromise the stability of aquatic infrastructure. Various MIC mechanisms require completely different physical and chemical conditions, but what they have in common is that they either directly or indirectly promote the key reaction in the corrosion of ironcontaining metals: Fe 0 / Fe 2+ + 2e − .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased hydrodynamic resistance, caused by drag forces from the roughened ship hulls, raises fuel consumption and leads to higher emissions and costs for fuel (by up to 40%) 5 as well as time-and resource-consuming cleaning procedures. 4,6,7 Some microorganisms, e.g., sulfatereducing (SRB), sulfur-oxidizing (SOB), iron-oxidizing (IOB), or iron-reducing (IRB) bacteria, can cause MIC through their bio-lms and metabolic products, 8,9 and thus compromise the stability of aquatic infrastructure. Various MIC mechanisms require completely different physical and chemical conditions, but what they have in common is that they either directly or indirectly promote the key reaction in the corrosion of ironcontaining metals: Fe 0 / Fe 2+ + 2e − .…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 Some microorganisms, e.g. , sulfate-reducing (SRB), sulfur-oxidizing (SOB), iron-oxidizing (IOB), or iron-reducing (IRB) bacteria, can cause MIC through their biofilms and metabolic products, 8,9 and thus compromise the stability of aquatic infrastructure. Various MIC mechanisms require completely different physical and chemical conditions, but what they have in common is that they either directly or indirectly promote the key reaction in the corrosion of iron-containing metals: Fe 0 → Fe 2+ + 2e − .…”
Section: Introductionmentioning
confidence: 99%
“…In the limited studies on the topic, the corrosion acceleration due to IRB is attributed to the bacteria's ability to produce soluble ferrous irons through reductive dissolution of the protective corrosion film of insoluble ferric iron oxides on the steel surface, thereby exposing the alloy surface to aggressive ions in the environment [10,12,13]. However, a few laboratory studies have reported the protective effect of IRB [14,15]. Lee and Newman reported that even if biofilm coverage of the metal is incomplete, cumulative O 2 respiration from both planktonic and sessile cells rapidly depletes O 2 on the metal surface, thus inhibiting the galvanic process and corrosion [16].…”
Section: Introductionmentioning
confidence: 99%